(untitled) (Research, Society and Development, 2025)
Obstructive Sleep Apnea Syndrome (OSAS) is characterized by recurrent obstructions during the night that interrupt the passage of air and cause a drop in oxygen saturation, which has repercussions in neurological and cardiovascular disorders. Among them, we include recurrent increases in blood pressure that are given by a sympathetic response of refractory hypoxemia to obstructive sleep apnea. Treatment for sleep apnea is performed with continuous positive airway pressure (CPAP), its constant use prevents nocturnal hypertensive peaks, which can help in the treatment of Systemic Arterial Hypertension (SAH). The objective of this study was to evaluate whether the use of CPAP to correct OSAS reduces blood pressure in individuals with SAH. The study was an exploratory literature review, in which searches were carried out in the electronic databases Scielo, PubMed and Lilacs, of articles indexed in English and Portuguese, between the periods of 2012 to 2022. The descriptors used for the research were selected according to the DeCS and MeSH lists, the DeCS list: Obstructive sleep apnea, systemic arterial hypertension and continuous positive airway pressure, and according to the MeSH list: Sleep Apnea Obstructive, Hypertension, Continuous Positive Airway Pressure. Nine articles were found that passed the inclusion and non-inclusion criteria established by the authors and were analyzed for the main information. Of these, 6 articles pointed out benefits in relation to the use of CPAP to correct OSAS and SAH, but the use of positive pressure is still controversial, as there are many factors that interfere with treatment adherence, which, in turn, does not result in the Physiological effect expected for the treatment of both diagnoses. We emphasize the need for further studies in the area to more effectively analyze the repercussion of the use of CPAP for the adjuvant treatment of SAH.